2019
DOI: 10.1183/23120541.00056-2018
|View full text |Cite
|
Sign up to set email alerts
|

Peak oxygen uptake reference values for cycle ergometry for the healthy Dutch population: data from the LowLands Fitness Registry

Abstract: Peak oxygen uptake (V′O2peak) is recognised as the best expression of aerobic fitness. Therefore, it is essential that V′O2peak reference values are accurate for interpreting a cardiopulmonary exercise test (CPET). These values are country specific and influenced by underlying biological ageing processes. They are normally stratified per paediatric and adult population, resulting in a discontinuity at the transition point between prediction equations. There are currently no age-related reference values availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Our recommendation for people with obesity is describing the VO 2 max in absolute values (ml min −1 ) instead of relative to body mass. Then, comparison with the values of Mylius et al ( 2019 ) is possible, who provided absolute values for the VO 2 max that were based on the LowLands Fitness Registry, as well. An alternative would be calculating a person’s ideal body weight and then dividing the absolute value of VO 2 max by this ideal weight, after which comparison with our reference values is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our recommendation for people with obesity is describing the VO 2 max in absolute values (ml min −1 ) instead of relative to body mass. Then, comparison with the values of Mylius et al ( 2019 ) is possible, who provided absolute values for the VO 2 max that were based on the LowLands Fitness Registry, as well. An alternative would be calculating a person’s ideal body weight and then dividing the absolute value of VO 2 max by this ideal weight, after which comparison with our reference values is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The Norwegian HUNT study demonstrated a cross-sectional association between objectively measured VO 2 peak and levels of conventional cardiovascular risk factors in 20-to 90-year-old volunteers (2,368 men and 2,263 women) (7). Further cross-sectional studies confirmed age and sex as important determinants of cardiorespiratory fitness (8)(9)(10) and consistently confirmed higher age to be related to lower levels of aerobic fitness. Another study in 751 men and women aged 20-85 reported a linear decrease (8% per decade) in VO 2 peak for both sexes, starting from the age of 30 (11).…”
Section: Introductionmentioning
confidence: 83%
“…The biggest studies (more than 1,000 participants) using bicycle ergometry included in the systematic review were performed in the USA by Kaminsky et al (9), in Belgium by Buys et al (13), in the Netherlands by Mylius et al (14) and Van de Poppe et al (15). Buys et al (13) published results of the oxygen uptake efficiency slopes of 1,411 healthy 20-60-year olds from the UP-LIFT study (friends, family, and colleagues).…”
Section: Discussionmentioning
confidence: 99%
“…Mylius et al (14) published reference values for the Dutch population. As a retrospective study of CPET using bicycle ergometry results from 4,477 subjects from 11 healthcare centres were studied, gas exchange analysis was done by bag collection, mixing chamber for breath by breath analysis.…”
Section: Discussionmentioning
confidence: 99%